Higher Education Opportunities in Sri Lanka - Karunathilake, I.M.; Edirisinghe, S.; Dias, N.W.G.L.T.L.; Senarathne, S.; Senanayake, S; Somaratne, G.T.S.V.; Gunawardhane, H.P.M.C; De Abrew, A. (The Organisation of Professionals Associations of Sri Lanka (OPA), 2022)
Strong human capital development is largely responsible for Sri Lanka's continued resilience as a nation in the face of major economic and political setbacks. Sri Lanka's higher education system has made significant contributions to the growth of human capital. Therefore, the country’s higher education strategy should focus on enhancing the system's positive aspects and resolving its problems. Opportunities for higher education should be based on human resources needs of the country and an evidence-based human resources management policy. Continuous improvement of higher education programmes through quality assurance, accreditation and based on current trends of educational science such as outcome-based, competency-based education, student-centered learning, integration, use of technology such as online learning and virtual reality.
Keywords: Higher Education; Sri Lanka